2019
DOI: 10.1007/s13201-019-1046-1
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and physicochemical parameters of outgoing waters in a pharmaceutical plant

Abstract: This work has focused on a pharmaceutical plant waters and the environmental impact of its discharges. The Water Quality Index (WQI), the Organic Pollution Index (OPI) and the Sodium Adsorption Ratio (SAR) of incoming and outgoing waters were analyzed over seasonal variations for 5 months using classical and mathematical indices. Highly significant increases were observed at the output (p < 0.001) for electrical conductivity, alkalinity, calcium and sodium; very significant (p < 0.01) for nitrites, COD and BOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Similar studies reported high rates of these quality parameters in raw wastewater influent at WW plants from Tunisia and Algeria, with values up to 1720, 1450, and 747 mg/L for COD, TSS, and BOD 5 , respectively [34][35][36]. In the other hand, other research showed that the average effluent content of several quality parameters like COD, BOD 5 , TSS, and NO 3 − showed an increase as compared to treated wastewater samples [37,38]. This result was linked to the performance and outcome of the wastewater treatment process used.…”
Section: Water Quality Monitoringmentioning
confidence: 68%
“…Similar studies reported high rates of these quality parameters in raw wastewater influent at WW plants from Tunisia and Algeria, with values up to 1720, 1450, and 747 mg/L for COD, TSS, and BOD 5 , respectively [34][35][36]. In the other hand, other research showed that the average effluent content of several quality parameters like COD, BOD 5 , TSS, and NO 3 − showed an increase as compared to treated wastewater samples [37,38]. This result was linked to the performance and outcome of the wastewater treatment process used.…”
Section: Water Quality Monitoringmentioning
confidence: 68%
“…A high concentration of free CO 2 , turbidity, and BOD and a low DO concentration indicate high organic loading, sedimentation, and microbial activities. [ 70,71 ] Thus, for PR‐2, the scores of all the underlying determinants of CCMEWQI, i.e., F1, F2, and F3, showed the highest values(Figure 5). The pollution level was found to be lower at PR‐1 relative to PR‐2 due to the dilution effect exerted by the influx of water from the river Ganga into PR‐1, which acts as the bridge between the river Saraswati and the Ganga at PR‐1.…”
Section: Discussionmentioning
confidence: 99%
“…While it is currently possible to collect in situ real-time quantitative data in fresh and wastewater systems for a plethora of physicochemical parameters, this is currently a challenge for waterborne pathogens [69][70][71]. At present, there is a lack of literature to back-up the practical concept of real-time data collection for waterborne pathogen populations except in water infrastructure facilities.…”
Section: Real-time Quantitative Datamentioning
confidence: 99%